Social Identities and Rivalries among Kaizer Chiefs and Orlando Pirates Online Football Fans in YouTube Podcasts - Admire Lesenga Maluleke; Mopailo Thomas Thatelo (COMMUSTY Journal of Communication Studies and Society, 2026)
The paper examines how Kaizer Chiefs and Orlando Pirates online fans are involved in participatory cultural agency through YouTube podcasts production and commentary in South Africa. Drawing on participatory culture framework integrated within a thematic critical analysis approach, the study analyses ten purposively selected YouTube podcast episodes from South African football fan channels active between January 2023 and March 2026. The paper adopts a qualitative interpretivist design. Study findings reveal that fans are not passive consumers of media, however, they are active cultural producers who creates, circulate and contest meaning through online podcast discourse. Through the thematic critical analysis, six themes emerged from data, namely: fan rivalry and identity, loyalty, love of the club, community and social cohesion, passion, and criticism of club management and performance. These themes collectively demonstrates that South African football fans deploy podcast platforms as spaces of participatory agency. They challenge mainstream sports media narratives, assert multilingual cultural identities and build local communities of practice. This paper address a significant research gap in African sports media research by centering South African football fandom in digital media scholarship.